Mimicry of lichens and cyanobacteria on tree-sized Amorphophallus petioles results in their masquerade as inedible tree trunks. (27th April 2019) - Claudel, Cyrille; Lev-Yadun, Simcha; Hetterscheid, Wilbert; Schultz, Matthias
Abstract: We revisit a case of mimicry in Amorphophallus involving visual mimicry of lichens and colonies of cyanobacteria on their tree-trunk sized petioles. We investigate the entire genus for similar defensive coloration types and report a defensive leaf coloration strategy in several Amorphophallus spp. that involves mimicry, camouflage and plant-mimicking that results in defensive visual masquerade. We propose that the visual expression of lichen and cyanobacteria mimicry enables the huge and fleshy petioles to look like solid non-edible tree trunks, a classic case of masquerade, probably as defence against herbivores. The results are discussed in a phylogenetic and evolutionary context.